Novel coumarin-based acetohydrazide-1,2,3-triazole derivatives as urease enzyme inhibitors: Synthesis, in vitro evaluation, and molecular dynamics simulation studies - Hassan Sepehrmansourie; Mohammad Azimi; Ahmad Ebadi; Gholamabbas Chehardoli; Mohammad Ali Zolfigol; Massoud Amanlou; Mohammad Nazari Montazer; Mohammad Mahdavi; Zahra Najafi (Heliyon)
Urease enzyme inhibition is a well-established and promising strategy for preventing the harmful effects of ureolytic bacterial infections, particularly those caused by H. pylori. However, acetohydroxamic acid, the only approved urease inhibitor, has limited use due to significant side effects, including teratogenicity and psycho-neurological symptoms. To discover new inhibitors, novel coumarin-based acetohydrazide-1,2,3-triazole derivatives were synthesized and evaluated for their urease inhibitory activity. All tested compounds displayed remarkable anti-urease activity (IC50 = 1.62–16.91 μM) compared to thiourea as reference standard (IC50 = 23.11 ± 1.02 μM). The most potent derivative,(E)-N'-(4-((1-Benzyl-1H-1,2,3-triazol-4-yl)methoxy)benzylidene)-2-((4,7-dimethyl-2-oxo-2H-chromen-5-yl)oxy)acetohydrazide (13a), acted as an uncompetitive inhibitor with a Ki of 1.99 μM. The stable enzyme-inhibitor complex in molecular dynamics simulations (MD) indicated critical interactions between the ligand and the Cys592 and His593 residues, which stabilize the flap motif of the enzyme. Molecular dynamics simulations suggested that compound 13a tends to remain near the SER579-HIS593 α-helix rather than the nickel ions, stabilizing it in an open state. Thus, the MD studies confirmed the proposed mechanism of uncompetitive inhibition. Overall, these findings highlight the potential of coumarin-based acetohydrazide-1,2,3-triazole hybrids as potent and novel inhibitors for developing new therapeutics against urease-related diseases.